Conservation status of the rare species Betula nana in the peatbog Tinovul Luci (the Harghita Mountains, Romania) - Borbély, Edina; Indreica, Adrian (Babes-Bolyai University Cluj-Napoca, 2019)
The aim of the study was to assess the conservation status of the boreal relict plant species Betula nana in one of the southernmost site of its range - the Natura 2000 site ROSCI0246 Tinovul Luci (Harghita county, Romania). Data collected in the field were confronted with that published in 1930 and 1960. Our findings show that Betula nana is critically endangered (CR) in the studied site, with a high risk of becoming extinct in the near future. The main threat is the change of habitat, which may be reversed, in part, by decreasing the cover of the tree layer
Keywords: Betula nana; biodiversity conservation; Natura 2000; peatbog